TRIM31 promotes Atg5/Atg7-independent autophagy in intestinal cells - Eun A. Ra (Nature Portfolio, 2016)
While non-canonical, Atg5/Atg7-independent autophagy has been reported to occur, molecular details of alternative autophagy pathways remain unknown. Here, the authors report that the protein TRIM31 mediates alternative autophagy in intestinal cells, which protects against pathogenic bacteria.